2007
DOI: 10.1021/jm0611253
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and in Vitro Gene Delivery Efficacies of Novel Cholesterol-Based Gemini Cationic Lipids and Their Serum Compatibility:  A Structure−Activity Investigation

Abstract: Five cholesterol-based gemini cationic lipids, which differ in the length of the spacer [-(CH2)n-] chain between the head groups, have been synthesized. These lipids are useful as nonviral gene delivery agents, and all cholesterol-based gemini lipids (2a-2e) are better transfecting agents than their monomeric lipid counterpart 1. Transfection efficiency of all the gemini lipids except lipid 2a [-(CH2)3-] was maintained even when the serum was present during the transfection conditions as compared to the monome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
125
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(127 citation statements)
references
References 37 publications
2
125
0
Order By: Relevance
“…Despite the high transfection efficacy of viral vectors, safety concerns have been raised in clinical trials. Non-viral vectors make a heterogeneous group of vehicles for gene transfer including cationic liposomes and polymers, which are considered to be less toxic, less immunogenic, and easier to handle than viral vectors, thus they are more attractive vectors for clinical applications (9)(10)(11)(12)(13). As the profound non-viral gene vector, polyethyleneimine (PEI) presents significantly high transfection capability in various cell cultures and in vivo gene transfer (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the high transfection efficacy of viral vectors, safety concerns have been raised in clinical trials. Non-viral vectors make a heterogeneous group of vehicles for gene transfer including cationic liposomes and polymers, which are considered to be less toxic, less immunogenic, and easier to handle than viral vectors, thus they are more attractive vectors for clinical applications (9)(10)(11)(12)(13). As the profound non-viral gene vector, polyethyleneimine (PEI) presents significantly high transfection capability in various cell cultures and in vivo gene transfer (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Other gemini-surfactants were specially synthesized for the usage as nucleic acids carriers into the cells (Kirby et al, 2003;) and the effects of the nature of the spacer, hydrocarbon chains, and headgroups on the transfection activity of these compounds were studied in detail. Dimeric lipids 14a-k, differing in the length of the spacer and the type of the cationic headgroup, were synthesized, and the transfection activity of these compounds was compared with this parameter for the monomeric lipids 3d and 3e (Bajaj et al, 2007a;Biswas et al, 2011). Lipids formed different aggregates, depending on the structure of the cationic head.…”
Section: Cholesterol Gemini-surfactantsmentioning
confidence: 99%
“…[31][32][33] Furthermore, a suitable spacer, in terms of length and nature, influences the gene delivery efficiency and serum compatibility of cationic liposomes. [34][35][36][37] Recently, we reported that the ionization states of the cationic head group influence the phase transition temperature, morphology, and transfection efficiency of the lysine-based cationic assemblies. 38 More specifically, lysine-based cationic assemblies with trifluoroacetic acid (TFA) salt as the counterion and a 3-hydrocarbon chain spacer between the lysine head group and the hydrophobic moiety showed the highest transfection efficiency in COS-7 cells.…”
Section: Introductionmentioning
confidence: 99%